2021
DOI: 10.3991/ijet.v16i14.21237
|View full text |Cite
|
Sign up to set email alerts
|

Issues of Educational Technologies and Authenticity Synergy in a Content and Language Integrated Learning Course at Technical University

Abstract: The issue of efficient technologies integration into educational environment has been a mainstream today. The present paper is focused on the issue of authen-ticity enhancement through learning technologies that are integrated into Public Relations course in the framework of Content and Language Integrated Learn-ing. Based on the questionnaire conducted among lecturers of the university, the authors analyzed teachers’ perception of authenticity and the ways of au-thenticity introduction in classes through educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…Some delved into students' experience in CLIL learning with the support of digital technologies (Galitsyna & Yesenina, 2020;Salekhova et al,2019;Zhao et al,2022). Some looked at the use of technology in designing and developing CLIL materials (Villarreal & Bueno-Alastuey, 2022;Zhyrun, 2016;Lavrysh et al, 2021). Others investigated the role of digital technologies in assisting CLIL pre-service teachers' professional development (Adipat, 2021), collaborative tasks and learning-to-learn competence (Garcia-Esteban et al,2021), student's motivation and engagement (Ángel,2015;Zaripova et al, 2019), and learning in a digital environment (Meinecke, 2020;Paliwoda-Pękosz & Stal, 2015).…”
Section: Summary Of Research Methodologies Used In the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some delved into students' experience in CLIL learning with the support of digital technologies (Galitsyna & Yesenina, 2020;Salekhova et al,2019;Zhao et al,2022). Some looked at the use of technology in designing and developing CLIL materials (Villarreal & Bueno-Alastuey, 2022;Zhyrun, 2016;Lavrysh et al, 2021). Others investigated the role of digital technologies in assisting CLIL pre-service teachers' professional development (Adipat, 2021), collaborative tasks and learning-to-learn competence (Garcia-Esteban et al,2021), student's motivation and engagement (Ángel,2015;Zaripova et al, 2019), and learning in a digital environment (Meinecke, 2020;Paliwoda-Pękosz & Stal, 2015).…”
Section: Summary Of Research Methodologies Used In the Studiesmentioning
confidence: 99%
“…However, this might raise a question about the authenticity of the materials. Given that awareness, Lavrysh et al (2021) addressed the issue by analyzing teachers' perceptions of authenticity and the ways authenticity was introduced in CLIL classes through educational materials and tasks. The authors found that accessibility to multiple digital resources helped teachers curate and develop materials with opportunities to link their teaching with the real world and add a variety of authentic learning activities.…”
Section: Content and Language Learnngmentioning
confidence: 99%
“…• Esta obra está bajo una licencia de Creative Commons Atribución-CompartirIgual 4.0 Internacional (CC BY-SA 4.0) https://creativecommons.org/licenses/by-sa/4.0/deed.es https://www.produccioncientificaluz.org/index.php/rvg Twitter: @rvgluz realización de las diversas actividades humanas; en consecuencia, para estar a la vanguardia de las necesidades e intereses del estudiantado actual, las tecnologías digitales tienen el potencial de ser una fuente poderosa para el proceso de sus aprendizajes (Eppard et al, 2021); por ello, los docentes deben utilizarlas de manera flexible y eficiente, incorporándolas como herramientas y recursos importantes en su ejercicio profesional (Lavrysh et al, 2021).…”
Section: Realidad Educativa En El Contexto Actualunclassified
“…En esta nueva realidad que se vive, los docentes deben continuar preparándose en el uso de las TIC, a fin de afrontar los retos que demanda la sociedad digital actual, teniendo en cuenta que esta nueva forma de educar vino para permanecer y formar parte de las competencias profesionales de los docentes; asimismo, las autoridades competentes deben promover programas de formación online sobre el uso de recursos digitales, para que estos profesionales se encuentren en sintonía con sus estudiantes (Holotescu et al, 2020), y puedan realizar sus clases virtuales de manera efectiva y eficiente. Existen estudios que refieren que el uso de la tecnología educativa ofrece a los docentes la oportunidad de acortar la distancia entre el salón de clase y el mundo real; así también, incorporar en su praxis una gran variedad de actividades motivadoras y auténticas de aprendizaje, las que permitan transformar la percepción que tienen los estudiantes sobre el factor enseñanza, que pasa de ser teórica a una experiencia práctica y atractiva para ellos (Lavrysh et al, 2021).…”
Section: Realidad Educativa En El Contexto Actualunclassified